Isolation and characterization of a novel Tenacibaculum species and a corresponding bacteriophage from a Mediterranean fish hatchery: Description of Tenacibaculum larymnensis sp. nov. and Tenacibaculum phage Larrie - Tsertou, Maria Ioanna; Triga, Adriana; Droubogiannis, Stavros; Kokkari, Constantina; Anasi, Grammatiki; Katharios, Pantelis (Frontiers in Microbiology, 2023)
Tenacibaculum larymnensis sp. nov., a novel species of the Tenacibaculum genus was isolated from a commercial fish hatchery in Greece. The novel species is phylogenetically close to T. discolor and was biochemically and genetically characterized. The genome of T. larymnensis has 3.66 Mbps length, 31.83% GC content and the genomic analysis demonstrated that it harbors a wide enzymatic repertoire suggestive of increased degrading capacity but also several virulence factors including hemolysins, secretion systems, transporters, siderophores, pili and extracellular proteins. Using the novel strain, a virulent bacteriophage designated as Tenacibaculum phage Larrie was isolated and characterized. Larrie is a novel Siphovirus with relatively large genome, 77.5 kbps with 111 ORFs, a GC content of 33.7% and an exclusively lytic lifestyle. The new phage-host system can serve as an efficient model to study microbial interactions in the aquatic environment which contribute to the nutrient cycling.